The Role of Formononetin in Osteoblast Function and Mineralization Potential with Deproteinized Bovine Bone Material - Ebru Haciosmanoglu Aldogan; Deniz Başaran; Bilgin Öner; Başak Günçer (Current Issues in Molecular Biology)
Objectives: Dental bone formation involves various cellular and molecular mechanisms, and phytoestrogens such as formononetin (FORM) are promising because of their estrogenic, anti-inflammatory, and antioxidant effects. This study investigated the effect of FORM on osteoblast proliferation, differentiation, and mineralization in combination with spongiosa granulates (BO) in vitro. Materials and Methods: Human fetal osteoblast cells (hFOB1.19) were treated with increasing concentrations of FORM (1, 10, and 100 µg/mL), BO, or their combination. Cell proliferation was assessed using a MTT assay. Alkaline phosphatase (ALP) activity, intracellular Ca2+, and Pi levels were measured using ELISA. Vascular endothelial growth factor (VEGF) and osteocalcin expression levels were analyzed by western blotting. Results: Cell proliferation increased with FORM, with or without BO, after 6 days (p < 0.001). FORM and BO had a synergistic effect on ALP activity (p < 0.001). Intracellular Ca2+ and Pi levels were highest in the BO-FORM group, suggesting superior mineralization (p < 0.05). VEGF and osteocalcin expression was significantly upregulated with FORM, alone and with BO (p < 0.05), indicating improved angiogenesis and bone maturation over 9 days. Conclusions: FORM enhances osteoblast proliferation, differentiation, and mineralization potential, particularly in BO spongiosa granulates. These data support the in vitro potential of formononetin-phytoestrogen in promoting osteoblast differentiation and mineralization potential with BO. These findings suggest that FORM, combined with BO, could improve bone augmentation in clinical applications such as maxillofacial surgery. FORM shows valuable potential for clinical applications, such as maxillofacial surgery, by promoting faster and more effective healing.